Nitric oxide releasing poly(vinyl alcohol)/S‐nitrosated keratin film as a potential vascular graft. Issue 5 (3rd December 2022) - Liu, Xu; Wang, Chenshu; Du, Mingyu; Dou, Jie; Yang, Jinyu; Shen, Jian; Yuan, Jiang
Abstract: Nitric oxide (NO) releasing vascular graft is promising due to its merits of thromboembolism reduction and endothelialization promotion. In this study, keratin‐based NO donor of S‐nitrosated keratin (KSNO) was blended with poly(vinyl alcohol) (PVA) and further crosslinked with sodium trimetaphosphate (STMP) to afford PVA/KSNO biocomposite films. These films could release NO sustainably for up to 10 days, resulting in the promotion of HUVECs growth and the inhibition of HUASMCs growth. In addition, these films displayed good blood compatibility and antibacterial activity. Taken together, these films have potential applications in vascular grafts.